ART AND CRAFT ACTIVITIES FOR EARLY CHILDREN TO IMPROVE FINE MOTOR ABILITY - Nurjanah, Inne; Mawardah, Mutia; Dian Purnamasari, Susan; Oktaviani, Nia; Yulianingsih, Evi (LPPM Univ. Ibn Khaldun Bogor, 2023)
Precision and good coordination are needed to move small muscles with fine motor abilities. Fine motor abilities are used in actions including cutting, tearing, folding, pasting, and putting together small things. Finger muscles, or fine motor abilities, are needed for this task. Early skill development is necessary to prepare children for their eventual entry into the world of formal education. Children aged 0 to 6 are considered to be in the early childhood period. The development that must be accomplished by the time a child turns 3 years old is already complex. Children need appropriate stimulation starting at that age to promote growth and physical development so that their abilities match the phases of age development. Through arts and crafts, children's fine motor skills can be improved. Activities involving art and crafts can be used to express oneself or as a component of aesthetics and creative expression. Since art and craft activities are tied to the creation of art, which requires strong finger muscles as well as good eye-hand coordination, they are beneficial for promoting the growth of fine motor skills in children.